Developing countries : urban & passenger transport - Seminar on Urban and Passenger Transport in Developing Countries (1986 : University of Sussex); Planning and Transport Research and Computation International Association; PTRC Summer Meeting (14th : 1986 : University of Sussex) (London : PTRC Education and Research Services, 1986)
08